Mobility Analysis of Kinematic Chains - Dargar, Ashok; Hasan, Ali; Khan, RA (Kathmandu University Journal of Science, Engineering and Technology, 2010)
In the present work a simple and efficient method is proposed to identify whether a kinematic chain posses total, partial or fractionated mobility. The proposed method uses the chain flow values (CFV) derived from the flow matrix of the given kinematic chain and successfully applied to all known cases of 2 and 3 degree of freedom planar kinematic chains. Since the method is systematic and efficient, it can be applied to the more complex chains which not have been reported in the literature yet. This study will be helpful in dividing the frame and input links from the view point of mobility. Some examples are provided to demonstrate the effectiveness of this method. Keywords: Degree of freedom (DOF); Contour; Chain flow value (CFV). DOI: 10.3126/kuset.v6i1.3307 Kathmandu University Journal of Science, Engineering and Technology Vol.6(1) 2010, pp25-32